The Impact of Targeted Regulation of Abortion Providers Laws on Abortions and Births - Grace E. Arnold (Global Labor Organization (GLO), 2022)
This paper analyzes the impact of supply-side abortion restrictions on aggregate abortion and birth rates in the United States. Specifically, I exploit state and time variation in the implementation of the first targeted regulation of abortion provider (TRAP) law in a state to identify the effects of the laws. I find that TRAP laws are associated with a reduction in the abortion rate of approximately 5% the year the first law is implemented, and an average reduction of 11-14% in subsequent years. There is also evidence that TRAP laws increased birth rates by 2-3%, which accounts for approximately 80-100% of the observed decline in abortion rates.
Keywords: I18; J13; J16; J18; 330; Abortion; Abortion Providers; Economics of Gender; Public Policy